Between elites and opposition: legislatures' strength in authoritarian regimes. Issue 6 (18th August 2021) - Wiebrecht, Felix
ABSTRACT: Virtually all authoritarian regimes have legislatures, and their role in bolstering regimes has been highlighted in recent research. Yet, the strength of authoritarian legislatures has received relatively little attention, although it can differ remarkably across regimes. This study utilizes an index of legislative strength to analyse parliaments in authoritarian regimes from 1946 to 2010. The empirical findings highlight that three factors are particularly important in predicting legislative strength, namely the level of personalism and the existence of an opposition and elections. However, beyond these factors, it appears that stronger legislatures are not generally associated with less authoritarian control over legislative and electoral processes. Yet, the findings also illustrate significant differences between de facto and de jure powers and across time periods. More competitive electoral and legislative procedures are linked to more de facto powers and stronger legislatures particularly after 1990. The findings contribute to our understanding of the institutional landscape in authoritarian regimes and provide a basis for future research on the effects of legislative strength.